How Concentrated are Global Infrastructure Markets? - Benitez, Daniel (World Bank, Washington, DC, 2012)
In infrastructure, the possibility of a positive relationship between operators' profitability and the degree of concentration is a major political issue in view of the wide diversity of feelings about the potential role of the private sector. This is particularly important in view of (i) the large residual degree of monopolies, (ii) the protection they are granted through exclusivity clauses built in service delivery contracts and (iii) the widespread sense that the same operators tend to be present in most of the privatized operations. The main purpose of this paper is to provide a first set of quantitative assessments of the degree of concentration in infrastructure at the global and at the regional level. Concentration issues were identified in only about 20 percent of the cases studied, a presumption of concentration was found in another 30 percent of the cases. We find no correlation between the degree of concentration and the degree of reform adopted by a region or a sector. In more general terms, we find no scope for simple encompassing regional or sectoral statements because issues are region- and sector-specific. We conclude by arguing that there are a few cases and regions in which it would make sense for a supranational competition or regulation agency to ensure that the interests of the users are protected more effectively against the risks of collusion and other types of anti-competitive behaviors local regulators would not be equipped to address.